Ars Moriendi; the art of dying well – new insights into the molecular pathways of necroptotic cell death. (27th January 2014) - Murphy, James M; Silke, John
Abstract When our time comes to die most people would probably opt for a quick, peaceful and painless exit. But the manner and timing are rarely under our direct control. Hence the Ars moriendi, literally, "The Art of Dying", two texts written in Latin around the 15th century that offered advice on how to die well according to the Christian ideals of the time. In contrast, for individual cells, the death process is frequently under their control and several signaling pathways that cause cell death, including apoptosis, pyroptosis and necroptosis, have been described. Furthermore the manner in which cells die can have good or bad consequences for the organism. In this review we will discuss how cells die via the necroptotic signaling pathway, with emphasis on recent structural work and place this work in a biological context by discussing relevant studies with knock‐out animals.